Dealing with populists in government: some comparative conclusions. Issue 2 (23rd February 2016) - Taggart, Paul; Kaltwasser, Cristóbal Rovira
Abstract : This conclusion summarizes the findings of the special issue and offers some comparative conclusions about what we can discover by examining the reactions to populists in government in Austria, Ecuador, Hungary, Italy, Poland, and Venezuela. Looking across this set of cases, we show that there is a diverse range of reactions to populists in power in terms of the actors involved, the strategies followed and their effectiveness. We start by summarizing the main ideas advanced in the framework for analysis of the special issue. After this, an overall assessment of the effectiveness of the opposition to populists in power is presented and here we offer an overview of each case study. Finally, the article concludes by proposing some comparative points, which not only seek to capture the main findings of this special issue but also to highlight the role of populists in actively developing strategies that curtail opposition.